1990
DOI: 10.1002/em.2850150208
|View full text |Cite
|
Sign up to set email alerts
|

Mutational specificity of alkylating agents and the influence of DNA repair

Abstract: Alkylating treatments predominantly induce G: C = greater than A:T transitions, consistent with the predicted significance of the miscoding potential of the O6-alG lesion. However, the frequency and distribution of these events induced by any one compound may be diagnostic. SN1 agents that act via an alkyldiazonium cation, such as the N-nitroso compounds, preferentially generate G: C = greater than A:T transitions at 5'-RG-3' sites, while the more SN2 alkylsulfates and alkylalkane-sulfonates do not. The precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(91 citation statements)
references
References 191 publications
6
84
0
1
Order By: Relevance
“…The persistence of O 6 -methylguanine adducts, resulting from alkylating agents, may cause DNA polymerase to misread the base pairing because of the altered hydrogen-bonding properties of a base that contains an additional methyl or ethyl group. Thus, O 6 -methylguanine is read as an adenine and mispairs with thymine (Horsfall et al, 1990). Supporting these data, the most common mutations caused by alkylating agents are G : C to A : T transitions (Horsfall et al, 1990), exemplified in the frequent generation of G to A transitions in the oncogene K-ras when the carcinogen N-methylnitrosourea (that forms O 6 -methylguanine adducts) is used in experimentally induced tumor systems (Sukumar et al, 1983;Mitra et al, 1989).…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 85%
See 1 more Smart Citation
“…The persistence of O 6 -methylguanine adducts, resulting from alkylating agents, may cause DNA polymerase to misread the base pairing because of the altered hydrogen-bonding properties of a base that contains an additional methyl or ethyl group. Thus, O 6 -methylguanine is read as an adenine and mispairs with thymine (Horsfall et al, 1990). Supporting these data, the most common mutations caused by alkylating agents are G : C to A : T transitions (Horsfall et al, 1990), exemplified in the frequent generation of G to A transitions in the oncogene K-ras when the carcinogen N-methylnitrosourea (that forms O 6 -methylguanine adducts) is used in experimentally induced tumor systems (Sukumar et al, 1983;Mitra et al, 1989).…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 85%
“…Thus, O 6 -methylguanine is read as an adenine and mispairs with thymine (Horsfall et al, 1990). Supporting these data, the most common mutations caused by alkylating agents are G : C to A : T transitions (Horsfall et al, 1990), exemplified in the frequent generation of G to A transitions in the oncogene K-ras when the carcinogen N-methylnitrosourea (that forms O 6 -methylguanine adducts) is used in experimentally induced tumor systems (Sukumar et al, 1983;Mitra et al, 1989). Avoidance of the mutagenic effect is directly related to the presence of a functional MGMT protein (Pegg et al, 1995).…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 99%
“…Alkylnitrosoureas preferentially cause GC4AT transitions at Gs preceded by a Pu residue in E. coli (Jurado et al, 1995;RoldaÁ n-Arjona et al, 1994;Richardson et al, 1987;Burns et al, 1988) and in eukaryotes (Inga et al, 1995;Kunz and Mis, 1989;Minnick et al, 1992;Moriwaki et al, 1991;Palombo et al, 1992). The 5'-¯anking purine eect has been explained as the consequence of a structural in¯uence on the initial formation of O6-alkylguanine, which may be further enhanced by alkylation speci®c repair (Horsfall et al, 1990). It is known that CCNU shows a sequence-dependent reactivity (Erickson et al, 1980;Briscoe et al, 1990;Hartley et al, 1986;Prakash and Gibson, 1992): the middle G in a run of three or more Gs is the most reactive.…”
Section: Discussionmentioning
confidence: 99%
“…So, Ada protein is able to decrease the mutagenic lesions induced by MNNG in H 2 O 2 -pretreated cells. Horsfall et al (1990) have shown that the DNA context influences both the distribution and reparability of alkylation damage. This observation may provide information on the cross-adaptive response between H 2 O 2 and MNNG, since the DNA alkylation pattern induced by MNNG can be altered when the DNA has already been oxidized.…”
Section: Cross-adaptive Response Between H 2 O 2 and Mnngmentioning
confidence: 99%